Chromosome 22q11.2 Deletion Syndrome Presenting as Adult Onset Hypoparathyroidism: Clues to Diagnosis from Dysmorphic Facial Features - Sira Korpaisarn; Objoon Trachoo; Chutintorn Sriphrapradang (Case Reports in Endocrinology)
We report a 26-year-old Thai man who presented with hypoparathyroidism in adulthood. He had no history of cardiac disease and recurrent infection. His subtle dysmorphic facial features and mild intellectual impairment were suspected for chromosome 22q11.2 deletion syndrome. The diagnosis was confirmed by fluorescence in situ hybridization, which found microdeletion in 22q11.2 region. The characteristic facial appearance can lead to clinical suspicion of this syndrome. The case report emphasizes that this syndrome is not uncommon and presents as a remarkable variability in the severity and extent of expression. Accurate diagnosis is important for genetic counseling and long-term health supervision by multidisciplinary team.